Algebraic Methodology and Software Technology - Meseguer, José (Springer, 2017)
This book constitutes the refereed proceedings of the 12th International Conference on Algebraic Methodology and Software Technology, AMAST 2008, held in Urbana, IL, USA, in July 2008.